V-Y flap as a treatment for lower lip bite - Lizbeth, Daza Villa Tavata; Luis, Villareal Salgado Jose; Hugo, Grano Gonzalez Victor; Gibran, Reyes Garcia Victor; Jesús, Vargas Montes Jose de; Emmanuel, Garcia Marin Gustavo; Esteban, Gaxiola Guarneros Luis; Yilzett, Reyes Gutierrez Mayra; Laura, Ramirez Soto Ana; Alexis, Ortega Fernandez (International Surgery Journal, 2023)
Dog bite wounds are problems that emergency centers around the world observe and treat frequently. The saliva of these animals is a potential pathological factor since multiple microorganisms are found in it, in addition to the fact that some of the lesions can deform facial symmetry with possible functional repercussions. This article aims to present the clinical case of a 12-year-old patient with a dog bite who underwent V-Y flap reconstruction.